Is impulsivity a common trait in bipolar and unipolar disorders?. (3rd January 2013) - Henna, Elaine; Hatch, John P; Nicoletti, Mark; Swann, Alan C; Zunta‐Soares, Giovana; Soares, Jair C
<x xml:space="preserve">Abstract</x> Henna E, Hatch JP, Nicoletti M, Swann AC, Zunta‐Soares G, Soares JC. Is impulsivity a common trait in bipolar and unipolar disorders? Bipolar Disord 2013: 00: 000–000. © 2013 John Wiley & Sons A/S.Published by Blackwell Publishing Ltd. Objectives: Impulsivity is increased in bipolar and unipolar disorders during episodes and is associated with substance abuse disorders and suicide risk. Impulsivity between episodes predisposes to relapses and poor therapeutic compliance. However, there is little information about impulsivity during euthymia in mood disorders. We sought to investigate trait impulsivity in euthymic bipolar and unipolar disorder patients, comparing them to healthy individuals and unaffected relatives of bipolar disorder patients. Methods: Impulsivity was evaluated by the Barratt Impulsiveness Scale (BIS‐11A) in 54 bipolar disorder patients, 25 unipolar disorder patients, 136 healthy volunteers, and 14 unaffected relatives. The BIS‐11A mean scores for all four groups were compared through the Games–Howell test for all possible pairwise combinations. Additionally, we compared impulsivity in bipolar and unipolar disorder patients with and without a history of suicide attempt and substance abuse disorder. Results: Bipolar and unipolar disorder patients scored significantly higher than the healthy controls and unaffected relatives on all measures of the BIS‐11A except for attentional impulsivity. On the attentional impulsivity measures there were no differences among the unaffected relatives and the bipolar and unipolar disorder groups, but all three of these groups scored higher than the healthy participant group. There was no difference in impulsivity between bipolar and unipolar disorder subjects with and without suicide attempt. However, impulsivity was higher among bipolar and unipolar disorder subjects with past substance use disorder compared to patients without such a history. Conclusions: Questionnaire‐measured impulsivity appears to be relatively independent of mood state in bipolar and unipolar disorder patients; it remains elevated in euthymia and is higher in individuals with past substance abuse. Elevated attentional and lower non‐planning impulsivity in unaffected relatives of bipolar disorder patients distinguished them from healthy participants, suggesting that increased attentional impulsivity may predispose to development of affective disorders, while reduced attentional impulsivity may be protective.